探討融入遊戲化設計之學習歷程如何影響不同學習動機學生的學習參與度 Exploring the Impact of Gamified Learning Portfolio on Student Engagement With Different Learning Motivations - 何淑君 Shu-Chun Ho; 李佩蓉 Pei-Jung Lee (National Taiwan Normal University, 2024)
學習動機是影響學習成效的重要因素，然而，高等教育所面臨的最大困境是學生缺乏學習動機。由於學生具備不同能力、興趣和動機，使得高等教育的教學場域面臨重大挑戰。本研究的動機在建立一個整合雙因子理論與遊戲化設計元素的課程設計架構，探討其如何影響不同學習動機學生在學習歷程中的參與度。研究目的在探討課程設計融入遊戲化設計元素與雙因子理論如何影響不同學習動機學生的學習參與度。本研究採混合式研究方法，透過動機問卷前測、觀察法、個案訪談及遊戲化設計後測問卷，對修課學生進行學習歷程分析。研究發現有四：一、遊戲化設計的激勵因子正向激勵內在動機高的學生。二、外在動機驅動的學習者受遊戲化設計驅動的影響較為全面，若在課程中加入遊戲化設計，會提升外在動機學生的參與度。三、保健因子中的損失趨避是遊戲化設計元素中影響無動機學習者的重要因素。四、激勵因子中的社會影響與關聯對內在動機驅動與外在動機驅動學習者皆發揮效果。據此，本研究之貢獻為提出一整合雙因子理論與遊戲化設計架構，為不同動機學習者提供課程設計 的參考。 Research Motivation and Objectives Learning motivation plays a critical role in enhancing learning effects and learning engagement. Lack of learning motivation among students is a widespread problem in higher education worldwide. The capabilities, interests, and motivations of higher education students vary, which makes it challenging to boost their learning motivation. The responsibility of higher education is not only to provide necessary knowledge and experience but also to foster students' self-directed learning and engagement. To achieve effective engagement, a voluntary mindset must first be cultivated, which is intimately linked to motivation. Motivation is a prerequisite for successful learning. However, motivation is a psychological state, which precludes its direct assessment through observations of internal or external stimuli. Therefore, this study investigates the effect of an integrated approach involving gamification design and two-factor theory on students' learning engagement in learning processes with different learning motivations. Theoretical Framework We propose a theoretical framework for curriculum design that integrates two-factor theory with gamification design. The proposed gamification design is based on the Octalysis framework, which involves the following eight drives of motivation (Chou, 2015; Moreira et al., 2020): epic meaning and calling, development and accomplishment, empowerment of creativity and feedback, ownership and possession, social influence and relatedness, scarcity and impatience, unpredictability and curiosity, and loss and avoidance. On the basis of two-factor theory, these eight drives were further divided into five motivators and three hygiene factors. This theoretical framework formed the foundation for the present study's analysis. Research Method The study employed a mixed-methods research approach. Students' learning processes were analyzed using a pretest motivation questionnaire, observations, case interviews, and a posttest gamification questionnaire. In total, 46 individuals attending a class on data analysis in a university were recruited. The study was conducted weekly throughout an 18-weeks semester. The data analysis curriculum was designed on the basis of the gamification design, with the intention of encouraging the students' learning engagement throughout the semester. Collecting student feedback is a crucial means of analyzing learning processes. Triangulation was employed to validate the accuracy of our findings. Quantitative and qualitative data on the same phenomenon from different perspectives were collected and analyzed. Findings After triangulating data from different research methods, the following findings were obtained. First, the motivational factors of gamification design positively influenced students with high intrinsic motivation. Second, students driven by extrinsic motivation were more comprehensively influenced by gamification design. Incorporating gamification into the curriculum enhanced engagement among students with extrinsic motivation. Third, among the hygiene factors of gamification design, loss and avoidance crucially influenced learners with no motivation. Fourth, among the motivational factors of gamification design, social influence and relatedness was effective for both intrinsically and extrinsically motivated learners. Contributions This study makes some salient contributions to the literature. The study proposes a theoretical framework that incorporates the two-factor theory to classify the eight gamification drives in the Octalysis framework into five motivators and three hygiene factors. This framework was used to investigate how gamification drives affect learning engagement in the relationship between gamification design and learning motivation. Second, the findings illustrate how gamification-driven course design affects the learning engagement of students with different types of learning motivations throughout their learning processes. These results inform the design of a curriculum that fosters the engagement of students with different learning motivations. Third, this study provides insights for curriculum design in higher education by proposing different gamification-driven approaches and strategies. Research Limitations and Future Research Directions This study was conducted in the context of a data analysis course administered in a university, and the results may not be fully generalizable to courses in different disciplines. However, the triangulation of pretest questionnaires, interviews, observations, and posttest questionnaires provides insights into how gamification design elements affect students with different learning motivations. Future research could explore and compare these effects across different disciplines in higher education.